ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMEL PADA PT BANK SYARIAH MANDIRI (Studi Kasus Pada PT. Bank Syariah Mandiri Cabang Ambon) - Risa Dewi Yanti Aceh; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTAnalysis of the Level of Health of a Bank by Using the Methods of the CAMELin PT. Bank Syariah Mandiri(Case Study on PT Bank Syariah Mandiri Branch Ambon)This research aims to find out and analyze the level of health of mandiri syariahbank. The method in use in the conduct of research that is by using the method ofCAMEL. Analysis of the the CAMEL has five aspects, namely the aspects ofcapital used CAR (Capital Adequacy Ratio), aspects of the quality of earningassets using the ratio of the KAP (Quality of Earning Assets), and PPAP(Productive Aseets Allowance), aspects ratio using management NPM (Net ProfitMargin),aspects ratio using earning ratios ROA (Return on Assets), and BOPO(Operating Income Against Operating Expenses), and aspect ratio using liquidityNCM-CA (Call Money to Current Assets), and LDR (Loan to Deposit Ratio). Thedata is collected in the report balance sheet, income statement and managementreport. Based on the results of research thathasbeen done on PT Syariah MandiriBank value CAMEL in 2011 82,92 is HEALTHY the year 2012 80,47 isHEALTHY, the year 2013 92,47 is HEALTHY, in 2014 72,43 is QUITEHEALTHY, and the last one 2015 74,76 is QUITE HEALTHY.Keyword : the health of th banks, capital, assets, management, earning, liqudity